The European Monetary System and international currency questions - Heinrich Matthes (Intereconomics, 1983)
As the recent struggles connected with the readjustment of exchange rates within the European Monetary System have shown, the relatively unproblematic “running in” period of the EMS, which was supposed to be a constructive contribution to the creation of a more viable international monetary system, is over. Dr. Matthes doubts that the EMS can live up to the original expectations and argues in favour of a restoration of the US dollar to its function as the key currency of the Western monetary system.
Keywords: 330; Monetary Policy